1983
DOI: 10.1039/f19837901649
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal catalysis. Transport versus surface control

Abstract: It has been shown that the flux of material diffusing to the surface of a colloidal particle is greater than to a plane surface of the same area and diffusion layer thickness (6). Around a small sphere of radius R the effective Nernst layer thickness deff is given by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Earlier studies have reported that electron-transfer reactions occur via colloidal particles . Under such conditions, the particles are found to pick up a mixed potential which is anodic to the reductant and cathodic to the oxidant . Such potentials depend on the size of the particle and the nucleophile present .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier studies have reported that electron-transfer reactions occur via colloidal particles . Under such conditions, the particles are found to pick up a mixed potential which is anodic to the reductant and cathodic to the oxidant . Such potentials depend on the size of the particle and the nucleophile present .…”
Section: Resultsmentioning
confidence: 98%
“…Nanoscale systems are an emerging field of research due to their ability to bridge the gap between the atomic and macroscopic scales. Any particle whose size falls in the range 1−100 nm can be called a nanoparticle whether it is dispersed in gaseous, liquid, or solid medium. These particles comprise clusters of small numbers of atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles were kept in suspension in a small reservoir by bubbling gas, and the dispersion was pumped through the flow circuit by using a Monostate Ministaltic pump. Typical flow rates were 15 cm s"1 2H20 + 2e ^H2 + 20H" (B) (B) and oxidation by (A) would require a fit of the experimental data to (30) or to the special case (A), (36).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction has been studied in considerable detail both theoretically [6][7][8][9][10][11][12] and by using various experimental techniques. [13][14][15][16][17][18][19][20][21][22][23][24] Nevertheless, studying the catalytic process (eq 1) experimentally poses severe problems due to the fact that MV 2+ is reduced at more negative potentials than protons under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%